Lattice Boltzmann Simulation of Droplet Formation in Non-Newtonian Fluids (Communications in Computational Physics, 2018)
Newtonian and non-Newtonian dispersed phase droplet formation in non-Newtoniancontinuous phase in T-junction and cross junction microchannels are investigatedby the immiscible lattice BGK model. The effects of the non-Newtonian fluidpower-law exponent, viscosity and interfacial tension on the generation of the dropletare studied. The final droplet size, droplet generation frequency, and detachment pointof the droplet change with the power-law exponent. The results reveal that it is necessaryto take into account the non-Newtonian rheology instead of simple Newtonianfluid assumption in numerical simulations. The present analysis also demonstratesthat the lattice Boltzmann method is of potential to investigate the non-Newtoniandroplet generation in multiphase flow.